2005
DOI: 10.1210/en.2005-0803
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Characterization of Pancreatic Islet Cells in the Mouse Insulin Promoter-Green Fluorescent Protein Mouse

Abstract: We recently reported a transgenic [mouse insulin promoter (MIP)-green fluorescent protein (GFP)] mouse in which GFP expression is targeted to the pancreatic islet beta-cells to enable convenient identification of beta-cells as green cells. The GFP-expressing beta-cells of the MIP-GFP mouse were functionally indistinguishable from beta-cells of normal mice. Here we characterized the ionic channel properties and exocytosis of MIP-GFP mouse islet beta- and alpha-cells. Beta-cells displayed delayed rectifying K+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 28 publications
9
106
6
Order By: Relevance
“…However, our observation that Kv2.1/Kv2.2 and BK account for the majority of Kv current in alpha cells suggests that Kv3 channels play only a minor role. Finally, Kv4.3 has been suggested to contribute a rapidly inactivating TEAinsensitive Kv current in mouse alpha cells [3,6,19]. We did not detect such a current in our preparation, and the Kv4.3 inhibitor phrixotoxin had no effect on alpha cell Kv currents in our hands.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, our observation that Kv2.1/Kv2.2 and BK account for the majority of Kv current in alpha cells suggests that Kv3 channels play only a minor role. Finally, Kv4.3 has been suggested to contribute a rapidly inactivating TEAinsensitive Kv current in mouse alpha cells [3,6,19]. We did not detect such a current in our preparation, and the Kv4.3 inhibitor phrixotoxin had no effect on alpha cell Kv currents in our hands.…”
Section: Discussioncontrasting
confidence: 55%
“…3c, d). Notably, we did not observe the TEA-resistant rapidly inactivating current component reported previously in isolated alpha cells [19] and alpha cells from intact islets [3]. In beta cells, inhibition of Kv currents with TEA augments insulin secretion in a glucose-dependent manner, since Kv channels contribute to action potential repolarisation [11,16,20].…”
Section: Methodscontrasting
confidence: 55%
See 1 more Smart Citation
“…8G0 . 1 pF respectively (Gopel et al 2000, Leung et al 2005. The criterion for b-cell identification in our experiment is that the whole-cell capacitance of the clamped cells is over 6 pF.…”
Section: Electrophysiological Recordingmentioning
confidence: 89%
“…The difference might be attributed to the unique biophysical properties of alpha cells. Numerous studies have demonstrated that: (1) alpha cell K ATP channels are more sensitive to ATP inhibition than those in beta cells; thus, the K ATP channels in alpha cells possess intermediate activity under low glucose concentrations [3,11,31,37]; (2) unlike the beta cell Na + channels, which are activated at a more negative membrane potential, the alpha cell Na + channels are active within a physiological range of membrane potentials [14,17,31]; and (3) in addition to the L-type Ca 2+ channels that are the most important in modulating [Ca 2+ ] i in beta cells, the activities of T-type and N-type Ca 2+ channels in alpha cells are critical in the generation of action potentials and control of glucagon secretion [11,14,15,38]. Based on these findings, it has been proposed that glucagon secretion only occurs within a narrow window of intermediate alpha cell K ATP channel activity (e.g.…”
Section: Discussionmentioning
confidence: 99%